2008
DOI: 10.1002/ar.20717
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis and Localization of mRNA Transcripts of Type I Collagen, Osteocalcin, MMP 2, MMP 8, and MMP 13 During Bone Healing in a Rat Calvarial Experimental Defect Model

Abstract: The study examined the expression of matrix metalloproteinases (MMPs), type I collagen and osteocalcin during bone healing in a rat calvarial experimental defect model. Twelve-week-old male Wistar rats were used. A full-thickness standardized trephine defect was made in the parietal bone, with the rat under anesthesia. RNA was extracted from tissue that filled the original bone defect on days 1 and 3 and in weeks 1, 2, 3, 5, 8, 10, 12, 18, and 24 and processed for quantitative analysis of expression of type I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…MMPs may be involved in calcification in bone development (Sasano et al , ). Our previous study showed that osteoblasts and osteocytes express MMPs 2, 8 and 13 as well as bone matrix proteins such as type I collagen and osteocalcin during bone healing in rat calvarial defects (Itagaki et al , ). Osteoblasts and osteocytes may degrade organic components by using MMPs and play a role in the remodelling of extracellular matrices during healing of bone, contributing to a decrease in organic components, as described above.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs may be involved in calcification in bone development (Sasano et al , ). Our previous study showed that osteoblasts and osteocytes express MMPs 2, 8 and 13 as well as bone matrix proteins such as type I collagen and osteocalcin during bone healing in rat calvarial defects (Itagaki et al , ). Osteoblasts and osteocytes may degrade organic components by using MMPs and play a role in the remodelling of extracellular matrices during healing of bone, contributing to a decrease in organic components, as described above.…”
Section: Discussionmentioning
confidence: 99%
“…39 Once the early osteoblast in-growth phase is completed, the entire cartilagenous zone is filled with osteoclasts and the intensity of the Col3.6 blue activity diminishes. The advancement of the Col3.6 blue cells presumably is dependent on the MMP13 that are highly expressed in early osteoblastic cells, 40 while the removal phase of the mineralized cartilage is dependent on the activity of the osteoclasts. The removal is critical for the final resolution of the fracture, as studies using agents that block osteoclast activity have a persistent unresorbed mineralized callus.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated MMPs during bone healing using a rat calvarial experimental model. The study examined the expression of MMPs, type I collagen and osteocalcin [26]. A full-thickness standardized trephine defect was made in the parietal bone of 12-week-old rats (Fig.…”
Section: Mmps In Bone Healingmentioning
confidence: 99%